História de vida pessoal e formação estudantil de uma professora do campo do nordeste paraense - TRINDADE, Patrícia dos Santos (2023)
Life history is currently an important source of information about professional teaching practice. In this way, the results of research carried out under this framework can greatly affect the initial training of teachers. Therefore, the objective of this research was to describe and analyze the personal and professional life trajectory of a Rural Education teacher, gathering information that may be useful in teacher training. The methodology and material consisted of a semi-structured interview, recorded, transcribed and analyzed, considering the theoretical framework of Life Stories and Teacher Training. The results indicate that there are intrinsic points to the person, such as their life process, which encompasses childhood and family aspects, as well as aspects that were of great relevance to the researched student teacher.